Diagnostic evaluation of central precocious puberty in girls - Shu-Nin Yeh; Wei-Hsin Ting; Chi-Yu Huang; Shih-Kang Huang; Yi-Chen Lee; Wei-Kian Chua; Chao-Hsu Lin; Bi-Wen Cheng; Yann-Jinn Lee (Elsevier, 2021)
Background: The gonadotropin-releasing hormone (GnRH) stimulation test is the gold standard for confirming the activation of the hypothalamic-pituitary-gonadal axis in central precocious puberty (CPP). However, it is time-consuming and costly. Our aim was to search for a simpler diagnostic modality for CPP by 1) evaluating the performance of basal serum luteinizing hormone (LH), 2) constructing a practical scoring system, and 3) determining the optimal single sampling time for serum LH in the GnRH stimulation test. Methods: Data of girls aged between 3 and 9 years at the time of the GnRH stimulation test, who attended our endocrine clinic at the MacKay Children's Hospital for signs of puberty between July 2014 and June 2019, were analyzed retrospectively. We recorded patients' age, height, weight, breast Tanner stage (BS), bone age, serum LH, and follicle-stimulating hormone (FSH). Receiver operating characteristic (ROC) curves and the Youden index were used to obtain the optimal basal serum LH level. Binary logistic regression was employed to construct a practical scoring system. Cross-sectional, cumulative frequency, and ROC curves were used to simplify the GnRH stimulation test. Results: Overall, 381 sets of GnRH stimulation tests were performed in 313 patients. Basal serum LH ≥ 0.2 IU/L demonstrated 70% sensitivity and 70% specificity for predicting positive GnRH stimulation test results. The practical scoring system (3 × BS + 3 × LH + 4 × FSH) showed 76% sensitivity and 72% specificity. The serum LH level at 30 min after intravenous gonadorelin exhibited 99% sensitivity and 100% specificity. Conclusion: Single sampling of serum LH at 30th minute post-injection of GnRH demonstrated a diagnostic performance equivalent to the traditional GnRH stimulation test in diagnosing CPP. Therefore, this approach could become the simplest diagnostic modality.